GOOD AGRICULTURAL PRACTICES BAWANG MERAH (Allium ascalonicum) DENGAN PUPUK KANDANG SAPI, TINJAUAN KEAMANAN PANGAN DARI ASPEK CEMARAN LOGAM BERAT - Sapto Priyadi; Setie Harieni; Tyas Soemarah Kurnia Dewi; Dwi Susilo Utami; Haryuni (JURNAL ILMIAH AGRINECA, 2021)
The aim of this research was to determine the effect of manure dosage treatment factors on shallot yield and heavy metal contamination of Pb, Cd, and Cu. Research factors include the use of cow manure, consisting of 9 levels of doses, namely: 0, 15, 20, 25, 30, 35, 40, 45, and 50 kg/ha. The results showed that the increase in manure dose was followed by an increase in the yield of shallot bulbs. The highest yield of shallot tubers (3,897.76) kg/ha was achieved in the treatment of doses of cow manure 50 kg/ha, the treatment was significantly different from the yield of shallot bulbs (3,634.73 kg/ha at the dose of manure treatment. cattle 45 kg/ha. While the lowest yield of shallots (1,875.86) kg/ha was achieved in the treatment of 0 kg/ha without manure. Heavy metal contamination on shallot bulbs in the dose treatment of cow manure 50 kg/ha consecutively: Pb (15,350) ppm, Cd (undetectable) detection limit of 0.01 ppm, and Cu (4,255) ppm. Heavy metal contamination on the shallot bulbs, among others, comes from the medium where the plants grow. Heavy metal content in the soil (pre-research) respectively: Pb (33.612), Cd (undetectable), and Cu (52.251) ppm. Meanwhile, the heavy metal content in manure added to the land consecutively: Pb (15,659), Cd (undetectable), while Cu (35,118) ppm.